The Mediating Role of Midwifery Support in the Association Between Tokophobia and Elective Caesarean Requests Among Primigravida: A Cross-Sectional Study - Neneng Siti Lathifah; Nurliyani Nurliyani; Fijri Rachmawati; Rochmawati Rochmawati (Yayasan Ahmad Mansyur Nasirah, 2026)
Fear of childbirth remains a significant psychological factor influencing delivery mode preferences among first-time pregnant women. This study aimed to examine the direct effect of tokophobia on non-medically indicated caesarean section (CS) requests among primigravidae and to assess the mediating role of midwifery support in this relationship. A cross-sectional design was employed involving 150 third-trimester primigravid women in Bandar Lampung City, selected through multi-stage cluster sampling across eight sub-districts. Tokophobia was measured using a culturally adapted version of the Wijma Delivery Expectancy Questionnaire Version A, while midwifery support was assessed using a researcher-developed instrument. Preferences for CS were collected through a nominal questionnaire. Data were analyzed using structural equation modeling with bootstrapping. The results showed that tokophobia significantly predicted both CS requests and the level of midwifery support. Furthermore, midwifery support significantly mediated the relationship between tokophobia and CS requests. Interestingly, the mediating effect was positive, indicating that supportive approaches lacking structured cognitive components may unintentionally reinforce CS preference among women experiencing fear of childbirth. These findings highlight tokophobia as a key psychological determinant of non-medically indicated CS demand in urban settings. In practice, integrating structured psychoeducational counseling and cognitive reframing techniques into routine antenatal care is crucial. Additionally, midwifery training programs should be strengthened to include evidence-based psychological intervention skills. Early screening for tokophobia, starting from the first trimester, is strongly recommended to help reduce unnecessary caesarean sections and improve maternal health outcomes.